Commercial banks’ response to government’s financial stimulus for improved agricultural financing in Nigeria - Yaro, Maryam; Olomola, Aderibigbe (International Food Policy Research Institute, 2015)
This study (i) examines the implementation of recent agricultural finance policies and incentives associated with the Nigerian Incentive-based Risk Sharing System for Agricultural Lending (NIRSAL) and the stimulus funds for boosting agricultural lending, the Commercial Agricultural Credit Scheme (CACS), (ii) determines the impact of these financial capital interven-tions (stimulus to the banking sector) through the instrumentality of CACS on the flow of credit to the agricultural sector, (iii) examines the factors militating against increased funding of agriculture by the banking sector, and (iv) articulates policies and strategies for improved participation of the banking sector in agricultural financing in Nigeria. The study was executed using data obtained from all the commercial banks in the country in a survey conducted between March and September 2013 plus secondary data covering the period from 2006 to 2012. The study focuses on two hypotheses, namely; (i) the stimulus provided by the government to the banking sector to boost agricultural financing has led to significant agricultural credit expansion; and (ii) commercial banks have been less risk-adverse to agricultural lending due to the capital infusion to the banking sector by the government to stimulate agricultural lending. These hypotheses were tested using random-effects Tobit econometric analysis.